Relasi Kebijakan Kriminal dan Hak Asasi Manusia dalam Upaya Penanggulangan Kejahatan - Randy Pradityo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The state has the authority to regulate how social organisations' activities are coordinated and directed towards national goals. This power is wielded through the legal system, with the help of the government and all its agents. The most important thing a country needs is power, which manifests itself in its ability to regulate the population (society) that lives on its territory. One of these arrangements can be seen in the government's anti-crime initiatives. Crime prevention efforts can be seen in crime statistics prepared by the Central Statistics Agency (BPS). According to crime statistics, the number of crimes committed in Indonesia is on the rise. As a result, it is critical to conduct research to combat crime by investigating the relationship between human rights and criminal policy. This study employs the normative research method. The goal of this study is to provide a fair assessment of criminal policy and crime prevention efforts. This legal research used both a statutory and a conceptual approach. Aside from using criminal channels, Indonesia must tackle crime by developing non-penal policies based on crime statistics. This non-penal policy may take a technological, cultural, moral/educational, global, or international cooperation approach, as well as a scientific one. What must be understood is that all crimes are the result of economic factors such as poverty and others. As a result, the government or state is expected to be present before the crime takes place to ensure the protection of citizens' human rights.